PENGGUNAAN MEDIA KARTU BERGAMBAR DENGAN MODEL STAD TERHADAP AKTIVITAS BELAJAR DAN PENGUASAAN MATERI OLEH SISWA - I Gede Suliwan; Arwin Achmad; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Mastery of the material is the result of learning in cognitive skills. The observations in class X Senior High School 15 Bandar Lampung mastery of the material by students is still low. This study aimed to determine the effect of media use picture cards with STAD learning model the activity and control of matter by students on the subject matter Virus. The study design is a pretest-posttest non-equivalent. Quantitative data obtained from initial test scores and final test dinalisis statistically using t-test at 95% confidence level. Qualitative data in the form of student activity data and questionnaire responses of students to use picture cards with model media STAD analyzed descriptively.The results showed the use of a picture card media with STAD learning model has influence on the increased activity of learning and mastery of the material by the students of class X SMA Negeri 15 Bandar Lampung on the subject matter Virus. The highest increase in the indicators of aspects of understanding are supported by studying the activity of the aspects of working with friends (90.7) and lowest indicator is the aspect of the analysis. Besides the increase is supported by the data questionnaire kemenarikan picture card media (88.29%) by stating that the students are happy, easier to understand, more active and motivated to learn to use the picture card media. It can be concluded that the use of a picture card media with STAD learning model has influence on the increased activity of learning and mastery of the material by the students of class X Senior High School  15 Bandar Lampung on the subject matter Virus.Keywords: picture card media, STAD, learning activities, mastery material, virus.